The Tendency of English Teachers in Teaching Grammar for Young Learners - Maria Setyaningsih Nernere (OKARA: Jurnal Bahasa dan Sastra, 2019)
Many language practitioners believe in the importance of grammar teaching for young learners as it supports the basic for young learners’ language development. Various beliefs on the grammar teaching method are aroused too. It leads to confusion on how to teach grammar in young learners’ classroom. Thus, this paper aims to investigate further how grammar is taught in young learners’ classroom. After having observations in sixth-graders’ English classes and deep interviews with the teachers who were observed, it is found that the teachers tended to teach grammar explicitly. It happened as they believed in the urgency of grammar mastery in the early ages. Moreover, they consider the students as those who are ready enough to understand the grammar rule as their logic is considered more advanced than their junior in school. This finding can be a means of supporting teachers’ self- evaluation, schools’ evaluation and also for other educational practitioners who want to investigate teaching grammar for young learners further.